Assessment of the Perception of the Clients on Data Privacy Observed by the Service Provider - Arcalas, Lilibeth Hiceta (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose— The study aimed to assess the perception of the clients on Data Privacy observed by the Service Provider to know the areas for improvement and provide better service, particularly on the observance of data privacy. Methods— The researcher adopted a descriptive research design and a structured questionnaire, which was distributed to 40 purposively selected clients. Data were analyzed using weighted mean calculations to determine the general sentiment regarding the company's data privacy practices. Results— The study revealed an overall mean score of 3.34, interpreted as slightly agree, indicating that clients moderately recognize the company’s efforts in securing personal data. While there is strong trust in the prevention of unauthorized access, concerns remain in areas such as data transparency, user control, and perceived risks associated with data handling. Implications— The results emphasize the necessity for the service provider to improve client involvement with data privacy through open communication and user-friendly privacy tools. To strengthen data privacy compliance and client trust, regular audits, client education initiatives, and the adoption of advanced security measures are recommended. Conclusion –There is a clear understanding on the part of the clients of how their data is secured, and the company can implement data security. Recommendations – It is recommended to have a qualitative approach to have strong support for the results of the survey. It is also good to study the privacy notice, consent form, data sharing agreement, security, retention and data disposal, privacy impact assessment, data protection policy, data breach response plan, and privacy management program.